Effectiveness of a Collaborative Care Intervention Between Pharmacies and Primary Care Targeting Hypertension and Hyperlipidemia: A Multicentre Quasi-experimental Controlled Trial (USFarmácia) - Costa, S (2019)
Context: The Study Team integrates researchers of: National Association of Pharmacies (ANF); NHS Primary Care Unit USF S. Julião of Agrupamento dos Centros de Saúde (ACeS) Baixo Mondego; National Oncology Registry (IPO Lisboa); Faculty of Pharmacy University of Lisbon; and Skaggs School of Pharmacy University of Colorado. The trial involves primary care and local pharmacies vs. usual fragmented care. Population: USF patients ≥ 18 years on medication for hypertension and/or hyperlipidemia. BackgroundThere is some evidence of health outcomes improvements of certain public health services provided by pharmacists in collaborative environments with physicians. This research uses: care protocols as decision algorithms in the pharmacy dispensing software; exchange of information technology-driven between settings and with patients; interprofessional meetings between pharmacists, physicians and nurses (Quality Circles). The project is the first in Portugal with such innovative features. MethodsThe trial started in March 2016. Baseline data collection and recruitment started in April 2018. End of recruitment in November 2018. Patients are followed for at least 6 months: hypertension and/or hyperlipidemia management in collaborative care by pharmacies and primary care. Intervention package: (1) point-of-care measurements at pharmacy/USF; (2) cardiovascular risk assessment at pharmacy/USF; (3) medication management at pharmacy/USF; (4) lifestyle counselling at pharmacy/USF; (5) referral and request for medical appointment from pharmacy to USF via IT; (6) feedback from USF and follow-up at pharmacy; (7) refill text reminders from pharmacy to patient (MED180®); (8) Quality Circles; (9) reporting adverse events to the National Pharmacovigilance System. Three data sources: pharmacy dispensing software and primary care extraction files in all available data points; patient telephone questionnaires at baseline, 3, and 6 months. Descriptive statistics for baseline characteristics, follow-up assessments, process and outcomes. Changes in outcomes will use GLM models and difference-in-difference estimators. At the time of this abstract: 6 Quality Circles involving 27 pharmacists, 5 physicians and 5 nurses and 276 patients recruited in 20 intervention and control pharmacies. End of 6-month follow-up data collection is due in May 2019 (+2 months). Impact of change on outcomesAssessment of changes at 6 months on: - Primary out-comes (disease control): blood pressure; total cholesterol; proportion of controlled patients. - Secondary outcomes (health behaviors): other cardiovascular risk factors in hyperlipidemia patients 40-65 years old; medication adherence and persistence; proportion of adherent patients. - Exploratory outcomes: related use of healthcare resources (incl. hospitalization), medication profile incl. medication burden; and patient satisfaction with care. Quality of life, preferences and cost data collected alongside trial for a separate economic study. Lesson points We expect to: Assess the effectiveness, process and patient experience/satisfaction of this collaborative care pilot; Test the feasibility of collecting a standard set of indicators in real world patients; Pave the way for the technology-driven exchange of meaningful outcomes between pharmacies and primary care. Published in: ICHOM 2019 Conference, 2-3 May 2019, Rotterdam, Netherlands.